Accessibility Study of Persons with Disabilities at Bandung Station – North Gate - Zumrati Aulia; Sally Octaviana (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2024)
The train station is a public function that can be easily accessed by various characters of ability (equitable space), responsive, and democratic by all users (Octaviana, 2019). Equitable space here refers to the equality of persons with disabilities in accessing space. There are 3 types of disabilities: mental disabilities, physical disabilities, and multiple disabilities. People with physical disabilities have limited movement according to their respective types of limitations. A friendly space for the physically disabled is created by applying the concept of universal design. The purpose of this study was to examine and find out how to design facilities for the needs of the physically disabled in accessing the accessibility provided by Bandung Pintu Utara Station. This research was conducted using a qualitative approach based on the diversity and ways of movement of persons with physical disabilities at the North Gate Bandung City Station. The data collection method was obtained through observation of the North Gate Bandung City Station facility. This research is expected to be input for designers and contribute knowledge about accessibility for physically disabled people.